IgG immunoadsorption reduces systemic lupus erythematosus activity and proteinuria: a long term observational study. Issue 7 (7th January 2005) - Stummvoll, G H; Aringer, M; Smolen, J S; Schmaldienst, S; Jiménez-Boj, E; Hörl, W H; Graninger, W B; Derfler, K
Abstract : Objective: To analyse the effects of rigorous immunoglobulin removal by immunoadsorption (IAS) on proteinuria (primary outcome variable), disease activity (SIS, SLEDAI, ECLAM), and autoantibodies to double stranded DNA (anti-dsDNA) in active systemic lupus erythematosus (SLE). Methods: 16 patients with severe SLE and renal disease, in whom cyclophosphamide was contraindicated or failed to halt disease progression, were treated with IAS for 3 months. Patients achieving at least 20% improvement in two or more of the outcome measures were considered responders and offered a 9 months' extension period. Results: Within 3 months, 14 patients responded and 11 opted for an extension. Proteinuria decreased from 6.7 (4.6) g/day (mean (SD)) at baseline to 4.3 (3.5) g/day at 3 months and 2.9 (2.4) g/day at 12 months (p<0.001). From baseline to 3 and 12 months, disease activity improved independently of scoring by SIS (15 (5) to 5 (2) and to 5 (2), p<0.0001), SLEDAI (21 (7) to 5 (4) and to 5 (4), p<0.0001), or ECLAM (7 (2) to 2 (1) and to 3 (1), p<0.0001). Anti-dsDNA fell from 391 (647) IU/ml to 146 (218) and to 53 (50) IU/ml at 3 and 12 months, respectively. Steroids could be tapered from 117 (159) mg/day at baseline to 29 (17) mg/day at 3 months and 9 (2) mg/day at 12 months. IAS was not associated with an excess of infections. However, one patient died of septicaemia after 1 month of treatment. Conclusion: In this negatively selected cohort of patients with SLE, IAS was associated with a significant response shown by reduced proteinuria, improved global disease activity, decreased anti-dsDNA, and lower glucocorticoid dosages, suggesting therapeutic benefit.